The Italian Eastern Border: About Lines, Areas and Volumes - Ivan Verč (Between, 2011)
A border encompasses three different meanings: a line to be defended or crossed, an empty area to avoid contact and a space which produces new meanings. Since the unification of Italy its eastern border has mostly been perceived as a line of conflict. Only for a few decades has it been devoid of violence. Its conflictual character is to be sought in a general cultural process which from the 6th to the 8th century saw Slav populations settle on the periphery of what was then the “centre” of the civilised world (Rome and Byzantium). The Slavs demanded recognition on an equal footing with the dominant model of civilisation, which considered the “Slav presence” as inferior. To move beyond a deep-rooted conflict it will be necessary to reconsider the border as a space with positive potential.